A numerical study of electrokinetically generated pre-earthquake geoelectric fields in layered porous media - Zheng, Xu-Zhen; Ren, Hengxin; Ren, Qinhan; Huang, Qinghua; Chen, Xiaofei (Geophysical journal international, 2025)
The investigation into the physical mechanisms and behaviour of geoelectric fields as potential precursors of earthquakes is a crucial yet challenging task in seismo-electromagnetics. Assuming the electrokinetic effect as a potential mechanism, we propose a novel numerical modelling algorithm based on the framework of the Luco-Apsel-Chen generalized reflection and transmission method to explore the behaviour of geoelectric fields in stratified porous media during earthquake preparation. This algorithm incorporates two innovative aspects: (1) employing the Jordan decomposition to address the degeneracy problem encountered in the quasi-static regime, and (2) utilizing digital linear filters for Hankel transforms to conduct the wavenumber integration. The accuracy of the algorithm in computing static displacements in an extremely low porosity half-space model is verified through comparison with analytical solutions. Numerical results from a half-space model demonstrate a strong consistency between the behaviour of the vertical electric field and filtration displacements. Notably, the maximum amplitude of the vertical electric field can reach approximately 3150.5 mV km−1, which is detectable by receivers located at considerable distances from the epicentre. In addition, three distinct types of pre-earthquake electric fields are identified: (1) the localized electric field induced by slow P waves, (2) the interface electric responses and (3) the direct converted electric field from the source. Results from a multilayer porous model show the significant influence of the water table on the amplitude of the vertical electric field. This can be attributed to the influence of water saturation and permeability on the coefficient that combines the vertical electric field and the vertical filtration displacement. We also analyse the temporal evolution of different fields during earthquake preparation, which demonstrates a robust correlation between the temporal characteristics of pore pressure and that of the vertical electric field. This indicates that the vertical electric field offers an effective means to detect pore pressure evolution. Furthermore, our analysis demonstrates that the broadening of electric anomalies can be used to roughly estimate the rate of stress accumulation. The sensitivity of the electric signal to the strike, rake and dip angles of potential faults indicates its ability to determine fault geometry related to an impending earthquake. These observations underscore the potential of using geoelectric precursors to study earthquake preparation mechanisms.